2011
DOI: 10.1016/j.cmet.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Measles Virus Nucleocapsid Gene and the SQSTM1/p62P392L Mutation to Paget's Disease

Abstract: Summary Paget's Disease (PD) is characterized by abnormal osteoclasts (OCL) that secrete high IL-6 levels and induce exuberant bone formation. Because measles virus nucleocapsid gene (MVNP) and the p62P392L mutation are implicated in PD, marrows from 12 PD patients harboring p62P392L and 8 normals were tested for MVNP expression and pagetic OCL formation. 8/12 patients expressed MVNP and formed pagetic OCL in vitro, which were inhibited by antisense-MVNP. 4/12 patients lacked MVNP and formed normal OCL that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 32 publications
2
134
0
Order By: Relevance
“…We previously showed that MVNP expression in OCLs induced a pagetic-like phenotype and pagetic-like bone lesions in mice (13,20). In contrast, mice with germline transmission of the mouse equivalent of the most frequent mutation linked to PD, p62 P394L , did not develop pagetic-like bone lesions (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that MVNP expression in OCLs induced a pagetic-like phenotype and pagetic-like bone lesions in mice (13,20). In contrast, mice with germline transmission of the mouse equivalent of the most frequent mutation linked to PD, p62 P394L , did not develop pagetic-like bone lesions (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…OCLs from patients with PD express high levels of IL-6 (8), and MVNP expression in OCLs induces high IL-6 expression levels that are essential for the formation of pagetic-like OCLs and bone lesions in MVNP-expressing mice (13). However, it is unknown whether IL-6 increases IGF1 expression, which would in turn increases ephrin B2 levels in MVNP mice.…”
Section: Il-6 Induces Igf1 Expression In Mvnp-expressing Oclsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although normal human osteoclasts in the bone contain three to ten nuclei per cell, pagetic osteoclasts contain up to 100 nuclei. Osteoclasts differentiated from human and mouse bone marrow cells overexpressing measles virus nucleocapsid protein (MVNP) gene, a causative gene for Paget's disease, contain more nuclei than the control osteoclasts (Kurihara et al, 2000;Kurihara et al, 2011). Cherubism is a dominantly inherited syndrome characterized by excessive bone resorption in the jaws and accumulation of inflammatory and/or fibrous tissue in the lower face.…”
Section: Introductionmentioning
confidence: 99%